Hypodontia in an adolescent with the HbSC genotype: a case report - F. A. OREDUGBA (Paediatric Dentistry, 2005)
Hypodontia, an anomaly of odontogenesis, may occur in isolation, or as a component of genetic or chromosomal defects [1,2] such as Down syndrome or ectodermal dysplasia. The majority of individuals with hypodontia have other signs which could be linked to their condition [3].